The Quality and the Complete Evidence Securing during the Traffic Crime Scene Investigation and its Relevance for Evidence Completion during the Traffic Accidents - Havaj, Peter (Communications - Scientific letters of the University of Zilina, 2018)
Main purpose of this paper is to point out the problems considering the modern scientific usage of methods, ways and approaches, including the crime investigation of traffic accidents-collisions. We want to show the basic need of experienced traffic crime detective, his/her deep knowledge of the whole issue - the process of the traffic accident perpetrating as a complex process with the direct impact on the traffic crime detective work, which could be used in the process of the clearance the case, the video-record output created by program PC CRASH as the virtual element of legal evidence, enabling deeper knowledge of the whole process.